Fertility Age Couples Motivation On Cervical Cancer Early Detection - Siti Nurul Khotimah; Dwi Ernawati (Universitas 'Aisyiyah Yogyakarta, 2021)
Cervical cancer is most often attacking women. After breast cancer, cervical cancer becomes second cancer infecting women. (WHO, 2014). This research aims to get the results from the fertility age couples' motivation on cervical cancer early detection.The preparation of a scoping review adapted the Arksey O'Malley framework consisted of 5 stages: research questions with the PEOs framework (Population, Exposure, and Outcomes), searching literature using relevant databases. The 12 articles used to consist of 3 themes, namely sexual and reproductive health problems, sexual health problems, and sexual and reproductive health.